PENGEMBANGAN MEDIA FLASHCARD “MITIGASI BENCANA ALAM” UNTUK MENGEMBANGKAN KREATIVITAS DAN KOMUNIKASI PESERTA DIDIK KELAS V SEKOLAH DASAR - Fatiya Sakinah; Yunimar Kholishah; Siti Fatonah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Flashcard media is a learning media that can help students understand their learning, especially in IPAS material. This study aims to analyze the feasibility of the